Investigation of genetic variability in natural Drosophila populations - Golubovsky, M.; Kaidanov, L. (Биополимеры и клетка, 1994)
The paper describes the origin and development of population genetics, its main discoveries achieved in experiments with Drosophila before 1948 breakage and summarized the results of two series of long-term studies on genetic variability in Drosophila carried out by the authors. The conceptual contribution of two main centers or school leaded by V. Kottzov and S. Chetverikov in Moscow and Yu. Filipchenko in St.-Petersburg is considered. The ideas and methodology of these schools were introduced into American and European genetics by Th. Dobzhansky and N. V. Timofeev-Ressovsky. A new approach to the description of the eukaryotic genome organizations is described. The authors argued that main source of the origin of various hereditary changes in nature is the interaction of environment with the facultative genomic elements. Статтю присвячено іcтopії виникнення та розвитку популяційної i еволюційної генетики i тих відкритів, які було зроблено в експериментах на дрозофілі за період до 1948 р., а також опису результатів двох серій довготривалих досліджень генетичної мінливості на дрозофілі, виконаних авторами. Розглянуто концептуальний i експериментальний внесок двох основних центрів, або шкіл, загальноі i популяційної генетики: московської (М. К. Кольцов i С. С. Четвериков) та петербурзької (Ю. О. Филипченко). Іх ідеї i методи були в подальшому інтродуковані до американської та европейської генетики Т. Добжанським i М. В. Тимофеевим-Ресовським. Представлено нове розуміння організації геному еукаріот та новий погляд на природу спонтанних спадкових змін, виникаючих переважно внаслідок взаємодії середовища з факультативними елементами геному. Статья посвящена иcтopии возникновения и развития популяционной i эволюционной генетики i тех открытий , которые были сделаны в экспериментах на дрозофиле за период до 1948 г., а также описания результатов двух серий долговременных исследований генетической изменчивости на дрозофиле , выполненных авторами. Рассмотрены концептуальный и экспериментальный вклад двух основных центров , или школ , общей и популяционной генетики : московской (М. К. Кольцов и С. С. Четвериков ) и петербургской (Ю. А. Филипченко ) . Их идеи и методы были в дальнейшем интродуцированные в американской и европейской генетики Т. Добжанским и М. В. Тимофеевым-Ресовским . Представлено новое понимание организации генома эукариот и новый взгляд на природу спонтанных наследственных изменений, возникающих в основном вследствие взаимодействия среды с факультативными элементами генома.